The Correlation Between Lecturers’ Teaching Styles and Students’ Reading Habit Towards Reading Comprehension (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Students’ reading habit and lecturers’ teaching in a classroom have a role to raise students’ achievement forbeing an important part of successful teaching and learning process. The aims of the research were toobserve 1) the lecturers’ teaching styles in teaching Extensive Reading class, 2) the students’ reading habit,and 3) the correlation between lecturers’ teaching style and students’ reading habit in readingcomprehension. The research employed a correlational research. Data sources were obtained from readinghabit questionnaire distributed to the students, teaching style survey based on Grasha-Riechmann to thelecturers, and TOEFL in reading test section to the students. The research indicated that 1) Lecturer 1 (D1)had moderate category as Expert and Facilitator, but high category for Formal Authority, Personal Model,and Delegator. Lecturer 2 (D2) had high category as Expert, Formal Authority, Personal Model, andDelegator, but moderate category for Facilitator. Lecturer 3 (D3) had high scores for five categories (Expert,Formal Authority, Personal Model, Facilitator, and Delegator), 2) the students’ reading habit category werefair, and 3) the lecturers’ teaching style was inversely correlated to reading comprehension. Reading habithad a proportionate relationship to reading comprehension. R value (0.661) indicated correlation betweenlecturers’ teaching style and students’ reading habit on reading comprehension is strong. Readingcomprehension skill should not be only observed from students’ reading habit, but also lecturers’ teachingstyle, for the success of learning and teaching in classroom.
Keywords: reading habit; teaching style; reading comprehension